Nuclear structure of the transactinides – investigated by decay spectroscopy - Heßberger Fritz Peter (EPJ Web of Conferences, 2016)
Superheavy elements owe their stability due to a subtle balance between the disruptive Coulomb force and the attractive nuclear forces. Thus they represent an ideal laboratory to study basic interactions. The essential tools are detailed investigations of radioactive decay properties and nuclear structure of superheavy nuclei. The results of those studies will deliver valuable input to improve theoretical models. To fulfill this demand conclusive data of high quality are necessary, which is presently not so easy to meet due to small production cross sections and technical limitations (beam intensities, detection probabilities). Possibilities and problems concerning extraction of decay properties and nuclear structure information on the basis of a low number of observed decay events will be discussed for three illustrative examples, 257Rf, 257Lr, and 288Fl.